Plasmin-mediated pericellular proteolysis by keratinocytes: extracellular matrix reorganization vs tissue damage - Kramer, Michael D.; Batrla, Richard; Hänsch, Gertrud Maria; Reinartz, Jeannette (Wound healing and skin physiology, 1995)
Plasminogen activators are specific proteolytic enzymes which convert the inactive proenzyme plasminogen to plasmin (Danö et al. 1985; Mayer 1990). Plasmin is a potent and nonspecific protease which cleaves fibrin clots (Collen 1980) and other extracellular proteins (Danö et al. 1985), including the glycoproteins of extracellular matrices (Cohen and Shuman 1990). The “plasminogen activator system” is complex; it consists of proenzymes of the plasminogen activators (PAs) (tissue-type PA (tPA), urokinase-type PA (uPA)), the PA substrate plasminogen, the active enzymes (uPA, tPA, and plasmin), several natural inhibitors of plasminogen activators and plasmin, and the cellular receptors that bind the proenzymes, enzymes and enzyme/ inhibitor complexes (Figs. 1, 3). The coordinated interactions of these components control location, timing, and extent of plasmin activity.